Patient Factors That Influence How Physicians Discuss Active Surveillance With Low-Risk Prostate Cancer Patients: A Qualitative Study. Issue 5 (September 2018) - Brooks, Joanna Veazey; Ellis, Shellie D.; Morrow, Emily; Kimminau, Kim S.; Thrasher, J. Brantley
For men diagnosed with prostate cancer, making treatment decisions can be overwhelming. Navigating treatment options, along with potential treatment side effects, can be difficult, and patients often rely heavily on the advice of their physicians. This study was aimed at understanding more about the way urologists talk with their patients about one treatment option: active surveillance (AS), a recognized management strategy for men with low-risk prostate cancer that includes close observation and monitoring of the cancer. This study reports, through 22 interviews with urologists, that urologists believe patients are hesitant about AS for a number of reasons, including misperceptions about cancer severity, anxiety, aversion to repeated biopsies that accompany AS, or family member preferences. Because urologists play an influential role in educating patients about treatment options, the discussion around AS can be impacted by barriers that physicians believe matter for their patients. Improving awareness among urologists about what factors impact their patient education about low-risk prostate cancer is important. Identifying tools to improve shared decision making in this area could result in treatment decisions that are increasingly concordant with patients' values, concerns, and goals.